Impediments to Acquisition of Building Drawing Skills by Undergraduate Technology Education Students in Nnamdi Azikiwe University - Nwachukwu, C. C.; Nwobi, F. C.; Auta, M. A.; Okoye, P. I. (Journal of Research in Industrial Technology and Educational Studies, 2026)
The study determined facility, teacher’s and student’s impediments to the acquisition of building drawing skills by undergraduate technology education students in Nnamdi Azikiwe University. Three research questions guided the study. The population of the study was 52 students. Census sampling technique was used for the study due to relatively small size of the population. The instrument used for data collection was 15 item structured questionnaire developed by the researchers. The instrument was validated by three experts. The reliability of the instrument was ascertained using Cronbach Alpha coefficient which gave 0.81. The researchers administered fifty-two copies of the questionnaire and retrieved the same number of copies after two weeks. Descriptive mean was used to analyze the data collected. The findings revealed among others that inadequate building drawing textbooks, lack of student-teacher interaction during building drawing lectures, and class sessions tend to be boring owing to non-use real building drawing plans while teaching. It was concluded that technology education learning facility should be kept in good order, teachers provided with all the teaching resources with incentives and students should spent quality time in learning the course. The study recommends among others that teachers should develop a means of arousing and sustaining students’ interest in learning building drawing skills while the students should embrace self-motivation in their efforts to comprehend and assimilate what they learnt.